2003-2004 IFPRI Annual Report: Agriculture, food security, nutrition and the Millenium Development Goals - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
The Annual Report contains an Essay: Agriculture, Food Security, Nutrition and the Millennium Development Goals by Joachim von Braun, M. S. Swaminathan, and Mark W. Rosegrant. There is an overview of the Institute followed by information on Research and Outreach. Special emphasis is given to Global Food System Functioning, Food System Governance, and Food System Innovations.